2018
DOI: 10.1242/dmm.031088
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal epithelial cell polarity defects in disease: lessons from microvillus inclusion disease

Abstract: The intestinal epithelium is a highly organized tissue. The establishment of epithelial cell polarity, with distinct apical and basolateral plasma membrane domains, is pivotal for both barrier formation and for the uptake and vectorial transport of nutrients. The establishment of cell polarity requires a specialized subcellular machinery to transport and recycle proteins to their appropriate location. In order to understand and treat polarity-associated diseases, it is necessary to understand epithelial cell-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 145 publications
(247 reference statements)
2
61
0
Order By: Relevance
“…As a proof of principle, we studied the dynamics of MVIs, the onset and elimination of which remain enigmatic. According to the 'combined' model of MVI onset (Schneeberger et al, 2018), the results of a recent paper using STXBP2 KO organoids (Mosa et al, 2018) and the results of the present study (Fig. 7), we showed that MVIs might arise by two main mechanisms: de novo nucleation in the cytoplasm or internalization of the PM.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As a proof of principle, we studied the dynamics of MVIs, the onset and elimination of which remain enigmatic. According to the 'combined' model of MVI onset (Schneeberger et al, 2018), the results of a recent paper using STXBP2 KO organoids (Mosa et al, 2018) and the results of the present study (Fig. 7), we showed that MVIs might arise by two main mechanisms: de novo nucleation in the cytoplasm or internalization of the PM.…”
Section: Discussionsupporting
confidence: 79%
“…For instance, whereas AP-1 is renowned for basolateral sorting in cultured cells (Gravotta et al, 2012), its crucial role in apical trafficking has been characterized in vivo in C. elegans and in mouse (Shafaq-Zadah et al, 2012;Zhang et al, 2012;Hase et al, 2013). Whereas the in vitro culture of intestinal organoids derived from patients with MVID or mice deficient in genes causing MVID (Schneeberger et al, 2018;Mosa et al, 2018;Wiegerinck et al, 2014) and the mutation of myoVb/goosepimples in zebrafish (Sidhaye et al, 2016) appear to reproduce most of the cellular and structural hallmarks of MVID, these models are not suitable for systematic studies. Conversely, the in vivo, easy-to-use and screening-amenable C. elegans model has been widely used to understand intestinal polarity mechanisms; however, single deletion of the orthologs of MVID-causing genes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A delicate, single layer of columnar epithelial cells joined by tight junctions function to selectively regulate the movement of solutes and ions to produce a highly effective, yet remarkably dynamic barrier. 1 The intercellular tight junctional complexes restrict the movement of potential therapeutic agents with a molecular mass of greater than~500 Da between adjacent epithelial cells; the so-called paracellular route. Thus, macromolecules that cannot travel through the paracellular route may be absorbed at the luminal surface of the epithelium through receptor-and/or fluid phasemediated uptake mechanisms, but their fate typically involves recycling back into the lumen and/or routing to the lysosomal degradation pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the route of application, apical versus the basolateral side of IECs, appears to influence DON-mediate changes in cell viability, as IPEC-J2 cell viability was more significantly affected when DON is applied to the basolateral side [157]. This differential susceptibility of apical and basolateral surfaces of IECs to DON exposure could be attributed to their biological and functional distinctions such as different protein and lipid compositions [172]. It could also result from the addition of the mucus produced by IPEC-J2 cells covering the apical side of epithelial monolayer [139] as an extra defense line against DON exposure.…”
Section: In-vitro Cell Culture Systemsmentioning
confidence: 99%